Development of Condition Indicator for Managing Sealed Rural Road Networks. Issue 1 (January 2015) - Rivera, Felipe; Chamorro, Alondra; Lucero, Robinson; Aravena, Claudio
Rural roads may be defined as low-volume roads that provide access and mobility to rural populations. In developing countries they commonly represent 80% of the total road network length and play a key role in economic and social development. Rural roads are divided into unsealed (gravel and earth) and sealed roads (roads with thin bituminous surfaces and stabilized roads). Network management methods recommend the use of objective condition evaluations, such as the pavement condition index and the unpaved roads condition indicator, to assist in decision making. However, none of these indicators properly apply to sealed rural roads; the performance of these roads is different because of climate and traffic demands. The lack of an objective indicator specially calibrated for sealed rural roads was addressed in this study. The main goal was to calibrate a condition indicator for managing sealed rural road networks. As a result of the study, a condition indicator that was preliminarily developed for double treatment surfaces was successfully validated for thin bituminous surfaces. In addition, a stabilized roads condition index (SRCI) was developed on the basis of field evaluations of various surface distresses observed in stabilized roads, which were contrasted with the evaluations of an expert panel. Two forms of the SRCI were calibrated: with and without roughness. Finally, a qualitative scale ranging from very good condition to very poor condition was defined for thin bituminous surfaces and stabilized roads, on the basis of the effect of three types of climates and roads hierarchy.